Effectiveness of cardiopulmonary resuscitation ventilation devices with protective hockey equipment as performed by certified athletic trainers - Konkol, N. N. (North Dakota State University of Agriculture and Applied Science, 2022)
Certified Athletic Trainers (ATCs) are expected to perform cardiopulmonary resuscitation (CPR) on athletes experiencing cardiac arrest regardless of the protective equipment worn by the athlete. Additionally, ventilation devices used by ATCs aide in the delivery of ventilations during CPR. The goal of this research was to determine which ventilation device allowed ATCs to deliver adequate ventilations and to establish recommendations for helmet removal method in hockey players requiring CPR. Twenty ATCs completed four scenarios of CPR according to the 2020 AHA guidelines using a PocketMask (PM) or FaceShield (FS) to deliver ventilations and accessing the airway by removing only the facemask or the entire helmet. Overall, the PM resulted in higher quality ventilations compared to the FS and complete removal of the helmet was superior compared to removing the only facemask. For hockey athletes requiring CPR, ATCs should remove the helmet completely and use a PM for ventilation delivery.